Vigor de las semillas y productividad de variedades de maiz - Tadeo-Robledo, M.=700 1 Espinosa-calderon, A.; Valdivia-bernal, R.; Gomez-Montiel, N.; Sierra-Macias, M.; Zamudio-Gonzalez, B.
(Es, En)
Ilus., 17 ref.
Keywords: ZEA MAYS; VARIEDADES; VIABILIDAD DE LA SEMILLA; MADUREZ; COSTA RICA; VARIEDADES CRISTALINAS; VARIEDADES DENTADAS; AGRONOMIA MESOAMERICANA